The Relation of Body Temperature and Vaginal Cytology Examination in Time Artificial Insemination Rate Fat-tailed Sheep (Ovis Aries) in The District Sidoarjo East Java - Anggriawan, Rhendyka Prasetya; Utama, Suzanita; Eliyani, Hana (KnE Life Sciences, 2017)
Ewes fertility is one aspect that needs to maximum level. Reproductive performance in sheep livestock in Indonesia has become one of the main determinants of reproductive success. This study has been carried out of the body temperature measurement and sampling of vaginal cytology of 60 fat-tailed sheep before artificial insemination in Sidoarjo East Java. Body temperature measurement is done in the rectum of reported ewes in heat and artificial insemination requested can be determined by observing the condition of the vulva of ewes such as the presence or absence of mucus through the vagina, vulva swollen and reddened vulva mucosa. vaginal cytology sampling with a cotton swab inserted into the vulva ± 15cm of ewes that reported in heat then interpreted by a microscope. The result showed that ewe’s body temperature in 39.1oC-39.2oC has a significant correlation with vaginal cytology type on oestrous phase. Keyword: Ewes, body temperature, vaginal cytology, the district Sidoarjo East Java